PENGARUH HOMILI PADA MISA HARI MINGGU BAGI PERKEMBANGAN IMAN UMAT DI PAROKI ST. CORNELIUS MADIUN - Mintan, Yullia; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
The homily aims to make the Catholics to aware of their faith in Christ, to nurture their spiritual life, and strenghten their relation with God. The research applied a qualitative method through interview. The respondents of research were Christian faithful in St. Cornelius Parish, Madiun City. Respondents regularly visiting the Church to attend Eucharist and listen to Sunday homily. The results of research indicated that there were 10 (100%) respondents disclosed that the homily on Sunday Eucharist celebration had a significant impact on the development of faith of the Catholics. Such developement was shown by the following indicators: 1) the Catholics were more active to go to the Church, 2) the Catholics become more diligent to read the Word of God, 3) the catholics become more diligent to follow any spiritual and social activities both within the Church and outside the Church, and 4) they were more diligent in carrying out the five tasks of the Church. Based on 10 respondents, there was only 1 (10%) respondent who said that the Sunday homilly has less impact on her life compared to the impact of receiving the holy body and blood of Christ (communion) during the Sunday Eucharist celebration.